Changes in the hydrodynamic characteristics of the upper layer of the South China Sea during the period of super typhoon Rammasun (2014). Issue 1 (1st January 2020) - Fu, Dongyang; Zhang, Xiaolong; Li, Xue; Liu, Dazhao; Yu, Guo; Xu, Huabing
Abstract: Severe typhoon Rammasun (2014) was strengthened (super typhoon) in the east of the Leizhou Peninsula before moving into the Beibu Gulf. This study used the empirical orthogonal function (EOF) method to analyze the spatiotemporal variations in the sea surface wind (SSW), surface level anomaly (SLA), sea surface temperature (SST), mixed layer depth (MLD) and precipitation of the SCS. The study found that this typhoon had a significant influence on the SSW, SLA, SST, MLD and precipitation changes. During the typhoon Rammasun, the spatial distribution of precipitation showed obvious 'left-hand-side intensification' relative to the typhoon track. However, the SST decreased rapidly, and cooling showed a clear 'right-hand-side intensification', and two cyclonic eddies in the southwestward were observed from the mode of EOF-1 of the SLA. The spatiotemporal variations of SST, MLD, SLA, SSW and precipitation during the period of super typhoon Rammasun were excellently reflected by the EOF method. The variabilities of SST, MLD, SLA, SSW and precipitation in the SCS during the typhoon period and the relationship between the variabilities were further analyzed.